The Effect of Land Slopes Covered with Paving Blocks on Rainwater Infiltration - Andi Marini Indriani; Gunaedy Utomo (Postgraduate, University of Mataram, 2026)
Rapid urban development has increased impervious surface coverage, causing higher surface runoff and reduced rainwater infiltration that contribute to flooding and groundwater depletion. Permeable pavement systems, such as paving blocks, are widely applied to support sustainable urban water management. This study analyzes the effect of land slope covered with hexagonal paving blocks on rainwater infiltration performance. Laboratory experiments were conducted using a rainfall simulator with a constant intensity of 50 mm/h. Three slope variations were evaluated, namely 0%, 2%, and 4%. The paving blocks had a compressive strength of 25 MPa (Class B) and were installed on a compacted sandy bedding layer. Infiltration and surface runoff volumes were measured at five-minute intervals until stable conditions were achieved. Results indicate that land slope significantly influences infiltration behavior. The highest infiltration performance occurred at a 2% slope, with a maximum infiltration volume of approximately 570 mL recorded between the 40th and 45th minutes. Conversely, the 0% slope showed decreased infiltration due to soil saturation, while the 4% slope exhibited lower efficiency because the increased slope accelerated surface runoff. These findings demonstrate that hexagonal paving blocks installed on a moderate slope enhance infiltration, reduce runoff, and support urban flood mitigation and groundwater recharge.